PENGARUH MANAJEMEN PEMBELAJARAN KEPALA SEKOLAH DAN KINERJA GURU TERHADAP HASIL BELAJAR MURID DI SMP NEGERI SE-KECAMATAN GAROGA TAHUN AJARAN 2025/2026ABSTRACT This study aimed to examine: (1) the effect of the principal's learning management on student lea - Rusli Ompusunggu; Iwan Setiawan Tarigan; Hasudungan Simatupang (STKIP Subang, 2026)
This study aimed to examine: (1) the effect of the principal's learning management on student learning outcomes, (2) the effect of teacher performance on student learning outcomes, and (3) the simultaneous effect of both the principal's learning management and teacher performance on student learning outcomes in State Junior High Schools throughout Garoga District, Academic Year 2025/2026. This study employed a quantitative approach with an associative research design. The population and sample consisted of all 87 teachers from six state junior high schools in Garoga District, selected using total sampling. Data on principal's learning management (X1) and teacher performance (X2) were collected through Likert-scale questionnaires, while student learning outcome data (Y) were obtained from the cognitive scores of the Final Semester Assessment (PAS) of Grade IX students as secondary data. Data were analyzed using simple and multiple linear regression. The results showed that: (1) the principal's learning management had a positive and significant effect on student learning outcomes (t = 7.145, Sig. = 0.000, R² = 0.375), contributing 37.5%; (2) teacher performance had a positive and significant effect on student learning outcomes (t = 9.064, Sig. = 0.000, R² = 0.492), contributing 49.2%; and (3) the principal's learning management and teacher performance simultaneously had a positive and significant effect on student learning outcomes (F = 76.830, Sig. = 0.000, R = 0.804, R² = 0.647), meaning both variables together contributed 64.7% to student learning outcomes. The resulting multiple regression equation is Y = 30.512 + 0.334X1 + 0.528X2.